Current approaches for integrating solution NMR spectroscopy and small-angle scattering to study the structure and dynamics of biomolecular complexes. Issue 9 (17th April 2020) - Delhommel, Florent; Gabel, Frank; Sattler, Michael
Abstract: The study of complex and dynamic biomolecular assemblies is a key challenge in structural biology and requires the use of multiple methodologies providing complementary spatial and temporal information. NMR spectroscopy is a powerful technique that allows high-resolution structure determination of biomolecules as well as investigating their dynamic properties in solution. However, for high-molecular-weight systems, such as biomolecular complexes or multi-domain proteins, it is often only possible to obtain sparse NMR data, posing significant challenges to structure determination. Combining NMR data with information obtained from other solution techniques is therefore an attractive approach. The combination of NMR with small-angle X-ray and/or neutron scattering has been shown to be particularly fruitful. These scattering approaches provide low-resolution information of biomolecules in solution and reflect ensemble-averaged contributions of dynamic conformations for scattering molecules up to megadalton molecular weight. Here, we review recent developments in the combination of nuclear magnetic resonance spectroscopy (NMR) and small-angle scattering (SAS) experiments. We briefly outline the different types of information that are provided by these techniques. We then discuss computational methods that have been developed to integrate NMR and SAS data, particularly considering the presence of dynamic structural ensembles and flexibility of the investigated biomolecules. Finally, recent examples of the successful combination of NMR and SAS are presented to illustrate the utility of their combination. Graphical abstract: Unlabelled Image Highlights: NMR and small-angle X-ray/neutron scattering experiments provide unique complementary information to study the structure and dynamics of biological macromolecules and complexes. Experimental approaches of NMR, small-angle X-ray scattering and small-angle neutron scattering, and computational methods to combine information from these techniques are discussed. Recent examples and applications illustrate the combination of NMR and small-angle scattering data for understanding important biological mechanisms.